Environmental information disclosure and firm valuation: corporate governance as moderating variable - Nofianti, Leny; Anitaa, Rizqa; Anugerah, Rita; Rasyid Abdillah, Muhammad; Balkish Zakaria, Nor (International Journal of Engineering and Technology, 2018)
Environmental issues have become an important topic in current accounting practice, especially in Indonesia. The government and public have been paying attention to this environmental issue for decades. The firm which discloses environmental information tends have been responded positively by investors. The response will tend to have an impact on firm valuation. Besides that the role of good corporate governance can also strengthen the relationship between environmental information disclosure and firm valuation. This study aims to examine the influence of environmental information disclosure on firm valuation. Specifically, this study investigates the effect of environmental information disclosure on firm valuation with corporate governance as moderating variable. Populations in this study were manufacturing firms listed in Indonesia Stock Exchange for the 2015 financial year and purposive sampling is used as a sampling method. The data were taken from firmâ€™s annual report. The result from PLS analysis reveals that environmental information disclosure affect firm valuation. In addition, the result also suggests that the effect of environmental information disclosure on firm valuations is moderated by role of corporate governance.Â Â